Vilniaus bastioniniai įtvirtinimai XVII-XVIII amžiuje - Girlevičius, Linas (Lietuvos istorijos studijos, 2007)
In 1648 the modernization of the defensive system of Vilnius town had been started. Preparing for a war with Moscow, it was planned to ring the capital of the Great Duchy of Lithuania with bastion fortifications. The best source to reconstruct the new concept of defense is the 1737 plan of Vilnius. The facts state that Vilnius was surrounded by two lines of defensive fortifications. The first line was equipped opposite the defensive town wall and served as reinforcement of this complex. In the second half of the 17th and the beginning of the 18th centuries, these bastion fortifications were urbanized - they were divided into plots. Their relations are not clear with the former additional fortifications of the defensive wall. The second line (the ring) of bastion fortifications was equipped distantly from the center of town. This line surrounded the territories of suburbia and access to the castles. Hypothetically we suppose the second defensive ring at least repeated the configuration of the former defensive control system. In the second half of the 17th century, the equipped second line of bastion fortifications could differ from the one depicted in the 1737 plan of Vilnius. Supposedly, Vilnius was planned to be ringed by solid fortification of bastions. It is certainly true that until the attack on the town by the Moscow army, the works were not finished. Hypothetical sections have been attempted to reconstruct by mapping burial grounds with massive graves of the middle of the 17th and 18th centuries. The facts state that people were massively buried in the surroundings of unusable or unequipped fortifications. The burial sites of victims of war and epidemic in the surroundings of fortifications could influence the establishment of town graveyards at the end of the 18th century until the beginning of the 20th century. The ramparts were reconstructed in the 18th century. Single fortifications were located in open sites outside the town. It is essential for further research and safeguarding of bastion fortifications as intellectual development of the Polish-Lithuanian state.